2020
DOI: 10.1021/acs.joc.0c01301
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Illudinine from Dimedone and Identification of Activity as a Monoamine Oxidase Inhibitor

Abstract: The fungal metabolite illudinine is prepared in seven steps and ca. 55% overall yield from dimedone using an “open and shut” (ring-opening and ring-closing) strategy. Tandem ring-opening fragmentation and olefination of dimedone establishes alkyne and vinylarene functionality linked by a neopentylene tether. Oxidative cycloisomerization then provides the illudinine framework. The key innovation in this second-generation synthesis of illudinine is the use of the nitrile functional group, rather than an ester, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…Biologically active quinolone and benzoacridinones, pyridine derivatives synthesized from cyclohexane-1,3-dione derivatives. [70,78,87,88]…”
Section: Synthesis Of 14-dihydropyridine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biologically active quinolone and benzoacridinones, pyridine derivatives synthesized from cyclohexane-1,3-dione derivatives. [70,78,87,88]…”
Section: Synthesis Of 14-dihydropyridine Derivativesmentioning
confidence: 99%
“…Benzoacridinones are another significant six‐membered nitrogen heterocycles that have tricyclic moiety containing acridine skeleton and showed different kinds of biological activities (Figure 3). [70] There are several methods in literature which provide benzoacridinones in the presence of catalysts such as N , N ‐disulfo‐1,1,3,3‐tetramethylguanidinium carboxylate ionic liquids, [71] sulfonic acid functionalized boron nitride, [72] and succinimide‐ N ‐sulfonic acid [73] . However, in spite of many advantages of these methods, they also have their limitations such as low yield and prolonged reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…Illudalic acid was isolated from the toxic eastern jack o’lantern mushroom, Omphalatus illudens , and was later discovered to be a selective phosphatase inhibitor . We recently reported that its congener, illudinine, is a monoamine oxidase inhibitor . The alcyopterosins are cytotoxic illudalanes from deep water Antarctic Alcyonium corals, which have received considerable attention from natural products researchers .…”
mentioning
confidence: 99%
“…Notable illudalane syntheses include that of illudalic acid and illudinine by Woodward and Hoye in 1977, that of illudinine by Teske and Deiters in 2008, that of alcyopterosin A by Sato in 2002 and by Iglesias in 2006, and those of several other alcyopterosins by Witulski in 2010 . We reported syntheses of alcyopterosin A in 2016 and illudinine in 2017, with the latter synthesis updated in 2020 . Eight additional publications on the synthesis of illudalane sesquiterpenes have appeared since the beginning of 2018, as these targets increasingly attract attention for natural product synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation